THE ROLE AND FUNCTIONS OF INTERNATIONAL ASSESSMENT PROGRAMS (PISA, PIRLS, TIMSS) IN THE NATIONAL ECONOMY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
In the context of the sharp intensification of global competition and the development of a knowledge-based economy, the quality of education has become a decisive factor for a country’s long-term economic stability and competitiveness. International assessment programs—PISA, PIRLS, and TIMSS—serve as important tools for objectively evaluating the effectiveness of education systems and for shaping strategies aimed at developing a nation’s human capital. This article analyzes the essence of these programs, their impact on the national economy, and the ways in which they provide guidance for the implementation of educational reforms.